Environmental Genocide and the Urgency to Criminalize Ecocide in Modern Criminal Law Reform - Zico Junius Fernando; Firdaus Arifin; Muhamad Adystia Sunggara; Chairul Huda; Fardana Kusumah (Administrative and Environtmental Law Review, 2026)
Environmental genocide refers to systematic ecological destruction that threatens the survival, identity, and dignity of particular communities, especially Indigenous and marginalized groups. This article argues that ecocide should be constructed as the legal offense capable of responding to such destruction within modern criminal law. Using a descriptive-prescriptive normative legal method, this study applies statutory, conceptual, and comparative approaches to examine the limits of existing environmental criminal law and to formulate a more precise model for criminalizing ecocide. The comparison focuses on the European Union, France, Ecuador, and Bolivia by assessing four variables: the definition of ecological harm, the threshold of severity, corporate and state accountability, and enforcement mechanisms. The study finds that Indonesian environmental law already recognizes serious environmental crimes and corporate liability, but it remains oriented toward pollution, administrative violation, and damage-based liability rather than systematic ecological destruction with cultural, intergenerational, and community-based consequences. This article proposes that ecocide be formulated as a distinct offense based on four core elements: unlawful or wanton conduct; severe, widespread, or long-term ecological damage; knowledge or intent regarding the risk of such damage; and aggravated liability where the destruction affects vulnerable communities or Indigenous peoples. The article contributes a doctrinal model for integrating ecocide into Indonesian criminal law reform through amendment of environmental legislation or the creation of a lex specialis on serious ecological crimes.